1991
DOI: 10.1016/0309-1651(91)90084-v
|View full text |Cite
|
Sign up to set email alerts
|

Some of eukaryotic elongation factor 2 is colocalized with actin microfilament bundles in mouse embryo fibroblasts

Abstract: Indirect immunofluorescent microscopy was used to study the distribution of eukaryotic elongation factor 2 (EF-2) in cultured mouse embryo fibroblasts. The perinuclear area (endoplasm) of all the cells and many straight cables running along the whole cytoplasm were stained with monospecific goat or rabbit antibodies to rat liver EF-2. Double staining of the cells with antibodies to EF-2 and rhodaminyl-phalloidin (used for actin microfilament detection) showed that EF-2 containing cables coincided with bundles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 14 publications
2
23
1
Order By: Relevance
“…The dephosphorylated state is the active form (Ryazanov et al, 1988 III, known as EF-2 kinase (Nairn and Palfrey, 1987), and dephosphorylated by PP2A (phosphatase 2A) (Michael et al, 1989). EF-2 is also known to be a GTP-binding protein (Kohno et al, 1986) and is colocalized with actin (Shestakova et al, 1991;Bektas et al, 1994). Surprisingly, the present work using Dd-EF2-null cells has revealed that the 101 kDa phosphoprotein is not required for protein synthesis and cell proliferation but it is involved in cytokinesis and the growth to differentiation transition.…”
Section: Introductioncontrasting
confidence: 58%
See 1 more Smart Citation
“…The dephosphorylated state is the active form (Ryazanov et al, 1988 III, known as EF-2 kinase (Nairn and Palfrey, 1987), and dephosphorylated by PP2A (phosphatase 2A) (Michael et al, 1989). EF-2 is also known to be a GTP-binding protein (Kohno et al, 1986) and is colocalized with actin (Shestakova et al, 1991;Bektas et al, 1994). Surprisingly, the present work using Dd-EF2-null cells has revealed that the 101 kDa phosphoprotein is not required for protein synthesis and cell proliferation but it is involved in cytokinesis and the growth to differentiation transition.…”
Section: Introductioncontrasting
confidence: 58%
“…Positive participation of 101 kDa Dd-EF2H in the process of cytokinesis would be a novel function. In connection with this, some of eukaryotic EF-2 is known to be colocalized with actin microfilament bundles in mouse embryo fibroblasts, which suggests a possible link between the protein synthetic machinery and the cytoskeleton (Shestakova et al, 1991;Bektas et al, 1994).…”
Section: Discussionmentioning
confidence: 80%
“…Early cell ultrastructural studies revealed an association between components of the translational machinery and the actin cytoskeleton (4,5), and functional studies showed that mRNAs associated with detergent-insoluble material, presumably the cytoskeleton, are translated more efficiently (6). Subsequently, it has been shown that virtually all of the protein components of translation associate with the cytoskeleton in situ (7)(8)(9)(10)(11)(12); however, no direct effect of the cytoskeleton on the specific activity of any of these co-factors has been demonstrated.…”
mentioning
confidence: 99%
“…A less well understood class of interactions involves association of the components of the cytoskeleton with the protein synthetic machinery. These include interactions of tubulin with EF-1A (Marchesi and Ngo, 1993;Durso and Cyr, 1994;Shiina et al, 1994) and interactions of actin filaments with the elongation factors 1A and 2 (Matsudaira, 1991;Yang et al, 1990;Demma et al, 1990;Dharmwardhane et al, 1991 ;Marchesi and Ngo, 1993;Edmonds, 1993;Gavrilova et al, 1987;Shestakova et al, 1991;Bektas , et al, 1994). In the present study, a combination of techniques were employed to characterise in vitro EF-2 and actin interactions and the interaction products.…”
Section: Discussionmentioning
confidence: 97%
“…In particular, a major actin-binding protein ABP-50 was discovered to be elongation factor 1A (EF-1A; Matsudaira, 1991;Yang et al, 1990;Demma et al, 1990;Dharmwardhane et al, 1991;Marchesi and Ngo, 1993;Edmonds, 1993). The presence of elongation factor 2 (EF-2) along actin microfilament bundles was shown using immunofluorescence microscopy (Gavrilova et al, 1987;Shestakova et al, 1991) and interactions between F-actin and EF-2 in vitro were demonstrated in co-sedimentation experiments (Bektas , et al, 1994). A stoichiometry of 0.12 EF-2/F-actin subunit was found at saturation levels, with the results suggesting binding at a single type of site with an apparent dissociation constant of 0.85 µM.…”
mentioning
confidence: 99%